Effects of Bupranolol, a New β-Blocker, on Platelet Functions of Rabbit and Human in Vitro - Umetsu, Teruhiko; Sanai, Kazuko; Kato, Tadakatsu (Thrombosis and Haemostasis, 1976)
The effects of bupranolol, a new β-blocker, on platelet functions were investigated in vitro in rabbits and humans as compared with propranolol, a well-known β-blocker. At first, the effect of adrenaline on ADP-induced rabbit platelet aggregation was studied because adrenaline alone induces little or no aggregation of rabbit platelets. Enhancement of ADP-induced rabbit platelet aggregation by adrenaline was confirmed, as previously reported by Sinakos and Caen (1967). In addition the degree of the enhancement was proved to be markedly affected by the concentration of ADP and to increase with decreasing concentration of ADP, although the maximum aggregation (percent) was decreased.Bupranolol and propranolol inhibited the (adrenaline-ADP-)induced aggregation of rabbit platelets, bupranolol being approximately 2.4–3.2 times as effective as propranolol. Bupranolol stimulated the disaggregation of platelet aggregates induced by a combination of adrenaline and ADP, but propranolol did not. Platelet adhesion in rabbit was also inhibited by the β-blockers and bupranolol was more active than propranolol. With human platelets, aggregation induced by adrenaline was inhibited by bupranolol about 2.8–3.3 times as effectively as propranolol.From these findings. We would suggest that bupranolol might be useful for prevention or treatment of thrombosis.